A Bioreductive Protecting Group for RNA Synthesis. Issue 9 (9th September 2021) - Saneyoshi, Hisao; Nakamura, Kodai; Terasawa, Kazuma; Ono, Akira
Abstract: This protocol describes a method for the preparation of ribonucleoside phosphoramidite bearing a bioreductive protecting group on the 2′‐OH group and its application in the synthesis of bioreduction‐responsive oligonucleotides. The protecting group used in this method consists of the modified 4‐nitrobenzyl skeleton, which has gem‐dimethyl groups at benzylic positions to enable deprotection under physiological conditions. Applying the synthesized ribonucleoside phosphoramidite to solid‐phase synthesis of oligonucleotides, a 2′‐O‐protected oligonucleotide was obtained without any undesirable cleavages under standard oligonucleotide synthesis conditions. The 2′‐O‐protected oligonucleotide was then treated with a combination of nitroreductase ( Escherichia coli ) and NADH as a bioreduction system for cleavage of the 2′‐O‐protecting group. After reduction of the nitro group, the protecting group was deprotected in a time‐dependent manner. Thus, this protection technology is a potential new tool for production of reduction‐responsive RNA‐based materials that can be used in life and medical sciences. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Synthesis of ribonucleoside phosphoramidite bearing a bioreductive protecting group Basic Protocol 2 : Synthesis of 2′‐O‐protected oligonucleotides and their deprotection properties under bioreduction